Analysis of the Influence of Transformational Leadership Style and Employee Competence on Work Productivity: A Random Forest Machine Learning Approach: Analisis Pengaruh Gaya Kepemimpinan Transformasional dan Kompetensi Karyawan terhadap Produktivitas Kerja: Pendekatan Pembelajaran Mesin Random Forest - Supatrem; Danang Aziz Akbarona; Junengsih (Jurnal Bisnis dan Ekonomi, 2026)
Objective : This study investigates the influence of organizational culture and leadership style on employee performance, with work motivation as a mediating variable at PT Indonesia Chemi-Con. A quantitative survey was conducted using structured questionnaires distributed to employees Methodology : Data were analyzed through path analysis to examine direct and indirect relationships among variables. Research results : The results show that organizational culture and leadership style have a significant positive effect on employee performance, both directly and indirectly through work motivation. A strong organizational culture enhances motivation and aligns employee behavior with company objectives, while participative leadership strengthens commitment and role clarity. Work motivation significantly mediates the relationship between culture, leadership, and performance. The study highlights the strategic importance of motivation in improving organizational effectiveness within the manufacturing sector. Future research should broaden variables and sample coverage to increase generalizability.